2019
DOI: 10.1016/j.injury.2019.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and complications of primary C-clamp stabilization or external fixation for unstable pelvic fractures

Abstract: Background and purpose Unstable pelvic fractures frequently require emergency stabilization using a C-clamp or external (CC/EF) fixation. However, the effectiveness of this intervention and associated complications are still a matter of debate. Patients and methods The analysis used data available from the German Pelvic Trauma Registry to study general complications, infections and mortality after primary stabilization using CC/EF in 5,499 patients (n=957 with vs n=4,542 without). Furthermore, the subgroups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
0
10
1
Order By: Relevance
“…We evaluated the effectiveness and the complications of the C-clamp compared to the pelvic binder only in type-C pelvic ring injuries. Regarding the fracture dislocation, which is discussed to be an indicator of injury severity and bleeding risk 15,19 , we could not find a significant difference between the pelvic binder and the C-clamp. While the group matching ensured that age and gender, and especially the initial hemodynamic conditions, such as initial blood pressure and initial HB level, were not different between the two groups, injury severity as a possible confounder was ruled out, since only patients p = 0.015; 0-6 h p = 0.028; 7-12 h p = 0.109; 13-24 h p = 0.260).…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…We evaluated the effectiveness and the complications of the C-clamp compared to the pelvic binder only in type-C pelvic ring injuries. Regarding the fracture dislocation, which is discussed to be an indicator of injury severity and bleeding risk 15,19 , we could not find a significant difference between the pelvic binder and the C-clamp. While the group matching ensured that age and gender, and especially the initial hemodynamic conditions, such as initial blood pressure and initial HB level, were not different between the two groups, injury severity as a possible confounder was ruled out, since only patients p = 0.015; 0-6 h p = 0.028; 7-12 h p = 0.109; 13-24 h p = 0.260).…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, Schmal et al 15 showed that mortality and complication rates after invasive emergency treatment (c-clamp and external fixator) are higher than in the non-invasive treatment group (pelvic binder). They attributed this observation to other risk factors, in particular age and ISS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…xator was established as the mainstay in treatment, while some others used PPP with C-Clamp in according with external xator (11,12). There is no evidence about comparing different types of surgeries.…”
Section: Introductionmentioning
confidence: 99%